Essentials of strength training and conditioning - Haff, Greg; Triplett, N. Travis (Human Kinetics, 2016)
This comprehensive resource, created by 30 expert contributors in the field, explains the key theories, concepts, and scientific principles of strength training and conditioning as well as their direct application to athletic competition and performance. The evidence-based approach and unbeatable accuracy of the text make it the primary resource to rely on for CSCS exam preparation.